Дослідження взаємозв’язку між енергією поверхні волокнистих наповнювачів та міцністю полімерних композицій на їх основі - Миронюк, Олексій Володимирович; Дудко, Володимир Андрійович; Баклан, Денис Віталійович; Смольниченко, Катерина Олександрівна (НТУ "ХПІ", 2016)
При конструюванні композиційних матеріалів є важливим прогнозування міцності матеріалу, що можна зробити за допомогою вивчення взаємозв’язку між силою адгезії та параметрами міцності. У роботі оцінено вплив термічної активації на значення поверхневої енергії вуглецевих волокон. Визначено вплив добавок: поверхнево-активної речовини EFKA 3299 та тетраетоксисилану на значення поверхневої енергії фенолформальдегідної матриці. За моделлю Оуенса-Вендта розраховано значення кутів змочування поверхні наповнювача матрицею та співвіднесені з механічною міцністю композицій.

For design of composite materials, it is important to predict its mechanical properties, which can be done by studying the relationship between the strength of adhesion, which can befound by experimental measuring of surface energy, and mechanical properties of the material. Nowadays relationships between these two parameters are still a field of debates. In this work we tried to clarify this question by analyzing the effect of additives that reduce wetting angle on the mechanical properties of the composite. The effect of thermal activation on the surface energy of a carbon fiber was estimated. The effect of additives the surface-active substances EFKA 3299 and tetraethoxysilane on the surface energy of the phenol-formaldehyde matrix was studied. Using the Owens/Wendt model, the values of the wetting angles of the filler surface by a matrix are calculated and correlated with the strength of the compositions.
Investigation of the relationship between the surface energy of fibrous fillers and the strength of polymer compositions based on them
Keywords: вуглецеве волокно; поверхнева енергія; модель Оуенса-Вендта; адгезія композиційних матеріалів; carbon fiber; Owens-Wendt model